(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This research focuses on the hero’s death in two Shakespearean plays, Othello and Romeo and Juliet. It attempts to answer how the author depicts death and dying in Shakespeare’s plays. Benstock and Dickinson, two specialists on death and dying, will provide an answer to the challenge. Benstock divides the death stages into three categories: deceased, moribund, and living-dead. Simultaneously, Dickinson mentions three periods of life: children strove (early life), gazing grain (physical maturity), and setting sun (ageing). This qualitative research uses textual analysis by deeply reading to describe the heroes’ deaths in the plays. The conclusion was that the hero’s death is simply a Shakespearean device for revealing the truth about anything. The message of peace is Romeo and Juliet’s death as a vehicle for unifying two opposing families, as in Romeo and Juliet’s tragedies between Capulet and Montague. It explains why there should be death when peace can be easily achieved. Furthermore, the revelation of truth through death confirms Desdemona’s loyalty to Othello.